The Effect Of Corporate Social Responsibility On Brand Awareness: The Case Study Of PT. Unilever Indonesia And Non-Governmental Organization (NGO) Spektra Surabaya - Habibi Dinil Haq (Trunojoyo University of Madura, 2021)
This research is motivated by the increasing number of companies using corporate social responsibility as a marketing strategy by involving the dimensions of business ethics and social impact around them to form a good image for the company. This study aims to determine the effect of corporate social responsibility on corporate image. This study uses a case study of PT Unilever Indonesia's corporate social responsibility collaboration with the Non-Governmental Organization (NGO) Spektra Surabaya in the form of the Gerakan Sikat Gigi Pagi Malam in ten sub-districts in Nganjuk Regency in mid 2010-2011. This study uses Corporate Social Responsibility (CSR) model as the analysis framework which consists of Community Support (X1), Diversity (X2), Employee Support (X3), Environment (X4), Non-US Operations / Not Only Operate in the Country of Origin (X5), and Products (X6) either jointly or partially on the company's image, as well as knowing which variables have dominant influence on the company's image. The type of research used in this research is explanatory research and the research method used is quantitative with the Slovin formula and purposive sampling technique.